Before the Normans : Southern Italy in the ninth and tenth centuries - Kreutz, Barbara M. (Middle Ages series., 1991)
Histories of medieval Europe have typically ignored southern Italy, looking south only in the Norman period. Yet Southern Italy in the ninth and tenth centuries was a complex and vibrant world that deserves to be better understood. In Before the Normans, Barbara M. Kreutz writes the first modern study in English of the land, political structures, and cultures of southern Italy in the two centuries before the Norman conquests. This was a pan-Meditteranean society, where the Roman past and Lombard-Germanic culture met Byzantine and Islamic civilization, creating a rich and unusual mix.